STRATEGI MANAJEMEN FULL DAY SCHOOL DALAM INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM - Firdiansyah; Sadan (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
The phenomenon of increasing popularity of Integrated Islamic Schools (SIT) with the Full Day School (FDS) system reflects new demands in the world of Islamic education, especially related to the internalization of religious values in a systematic, sustainable, and integrated manner in school life. Schools with the FDS system not only function as learning institutions, but also as a forum for the formation of students' religious character. This study aims to analyze in depth the management strategies applied in FDS in order to internalize the values of Islamic religious education, especially at the junior secondary education level. The method used is a qualitative approach with a case study type. Data collection techniques include in-depth interviews with principals, teachers, and students; participatory observation of religious activities; as well as documentation of work plans and character development programs. The results of the study show that the value internalization strategy is carried out through structured planning based on core values, habituation of daily worship such as prayer and tadarus, teacher role models in attitude and behavior, integration of Islamic values in the national curriculum, and evaluation of students' character involving the role of parents. Factors supporting the success of this strategy include the commitment of the school management, a conducive religious environment, and the active participation of parents. Meanwhile, inhibiting factors include student fatigue due to long learning durations, less supportive family backgrounds, and limited teacher training in character management. This study concludes that the success of internalizing Islamic values in the FDS system is highly dependent on the quality of adaptive, collaborative, and consistent strategic management.